Visual disturbances during pregnancy caused by central serous choroidopathy. - Cruysberg, J. R. (1982)
Three patients had during pregnancy visual disturbances caused by central serous choroidopathy. One of them had a central scotoma in her first and second pregnancy. The 2 other patients had a central scotoma in their first pregnancy. Symptoms disappeared spontaneously after delivery. Except for the ocular abnormalities the pregnancies were without complications. The complaints can be misinterpreted as pregnancy-related optic neuritis or compressive optic neuropathy, but careful biomicroscopy of the ocular fundus should avoid superfluous diagnostic and therapeutic measures.